2018
DOI: 10.1039/c7ra13293j
|View full text |Cite|
|
Sign up to set email alerts
|

CpG incorporated DNA microparticles for elevated immune stimulation for antigen presenting cells

Abstract: As emerging evidence supports the immune stimulating capability of the CpG oligodeoxynucleotides (ODN), CpG-based adjuvants have been widely used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 43 publications
(58 reference statements)
1
15
0
Order By: Relevance
“…Meanwhile, the same amount of self‐assembled CpG DNA microsphere (DMS) made up of CpG ODN was also used as a control group, which was introduced in our previous study. [14a] As expected, dsRMS‐70 treated cells showed the highest expression of IFN‐β among all types of RMSs with the release of dsRNA fragments by systemic degradation after cellular uptake. Taken together, it was confirmed that the RMS with 70 bp long‐dsRNA region would be able to induce moderate immune response from RAW264.7 cells.…”
supporting
confidence: 59%
See 3 more Smart Citations
“…Meanwhile, the same amount of self‐assembled CpG DNA microsphere (DMS) made up of CpG ODN was also used as a control group, which was introduced in our previous study. [14a] As expected, dsRMS‐70 treated cells showed the highest expression of IFN‐β among all types of RMSs with the release of dsRNA fragments by systemic degradation after cellular uptake. Taken together, it was confirmed that the RMS with 70 bp long‐dsRNA region would be able to induce moderate immune response from RAW264.7 cells.…”
supporting
confidence: 59%
“…On the other hand, the immunogenicity of self‐assemblies composed of DNA, RNA, or DNA‐RNA hybrid has been investigated widely for the better understanding of immunogenic properties of nucleic acid‐based structures and their clinical translation. However, the study of immune stimulating properties of self‐assembled RNA particles with potentially immunostimulatory RNA fabricated from RCT is not well established, whereas DNA particles from rolling circle amplification have been widely exploited as adjuvants for boosting immune response . In order to clinically translate the fast‐evolving RNA‐based therapeutics, evaluation of immune response to self‐assembled RNA particles is indispensable.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To broadly establish how the addition of these inhibitors impacts the antibody levels, we chose to analyze the total Ig (G+A+M) produced after 21 days ( 18 ). On day 21, we analyzed the anti-OVA antibody levels ( Figure 1D ).…”
Section: Resultsmentioning
confidence: 99%